La transtextualidad en los títulos de crédito en The Human Voice (2020) de Pedro Almodóvar - Dnda. Virginia HORNERO CAMPOS (Fonseca, Journal of Communication, 2023)
The human voice (Almodóvar, P. 2020) deals with human loneliness, specically the female one, through drama and woman’s despair who gives everything she has to let her love relationship go on, but who also does not hesitate to change what remains. Premiered at the Venice Festival, it is perhaps best Pedro Almodóvar’s work where a symbiotic relationship can be observed in which transtextuality (Genette’s term and theory commonly used in the literary eld) transcends to generate a puzzle in which the opening curtain of credits titles, with a magnanimous identity charge, will dialogue under Stvdio Gatti’s creativity,with the film of La Mancha’s director, without qualifying or complementing it.